Prognostic value of prognostic nutritional index score and controlling nutritional status score in patients with glioblastoma: A comprehensive meta-analysis - Peng, Jie; Li, Xiaoyu; Huang, Mingsheng; Ma, Mincai; Huang, Qin; Huang, Ning; Cheng, Yuan (Frontiers in Oncology, 2023)
Introduction: Previous studies have shown that some nutritional and inflammatory indicators can predict the prognosis of glioma. Among them, the prognostic nutritional index (PNI) score and the controlling nutritional status (CONUT) score may be valuable prognostic factors. The purpose of this study was to further evaluate the prognostic value of the PNI score and CONUT score in patients with high grade glioma. Method: A comprehensive search of PubMed, EMBASE and Web of Science databases included these articles that evaluated the prognosis of high grade glioma with PNI score and CONUT score. Result: Eleven articles were included in this meta-analysis, involving 1585 patients with high grade glioma. HR and 95% confidence interval of univariate analysis and multivariate analysis in these articles are extracted respectively. After a meta-analysis of univariate analysis data, it was shown that a high PNI score was a favorable factor for the overall survival (OS) (HR 0.49 [95% CI, 0.43, 0.56] I2=0%) and progression free survival (PFS) (HR 0.58 [95% CI, 0.48, 0.70] I2=0%) of high grade glioma patients, and low CONUT score was a favorable factor for OS (HR 2.39 [95% CI, 1.77, 3.23] I2=25%) of high grade glioma patients. After a meta-analysis of multivariate analysis data, a high PNI score (HR 0.61 [95% CI, 0.49, 0.76]; I2=13%) and low CONUT score (HR 2.79 [95% CI, 2.01, 3.89]; I2=39%) were favorable factors for OS in patients with high grade glioma. However, the PNI score was not significantly associated with PFS (HR 0.76 [95% CI, 0.57, 1.00]; I2=43%). Conclusion: PNI score and CONUT score may have prognostic value for patients with high grade glioma, but more large-scale studies are needed to verify.